High performance of solvothermally prepared VO2(B) as anode for aqueous rechargeable lithium batteries - Milošević Sanja; Stojković Ivana; Mitrić Miodrag; Cvjetićanin Nikola (Journal of the Serbian Chemical Society, 2015)
The VO2 (B) was synthesized via a simple solvothermal route at 160oC in ethanol. The initial discharge capacity of VO2 (B) anode, in saturated aqueous solution of LiNO3, was 177 mAh g-1 at a current rate of 50 mA g-1. After 50 cycles capacity fade was 4%, but from 20th-50th cycle no capacity drop was observed. The VO2 (B) has shown very good cyclability at current rate of even 1000 mA g-1 with initial discharge capacity of 92 mAh g-1. The excellent electrochemical performance of VO2 (B) was attributed to the stability of micro-nano structures to repeated intercalation /deintercalation process, very good electronic conductivity as well as the very low charge transfer resistance in the aqueous electrolyte. [Projekat Ministarstva nauke Republike Srbije, br. III45014]